From Human Resources to Business Growth: The Role of Skills, Motivation, and Compensation in Driving Driver Performance and Service Quality - Nanda Harifon; Rizaldi Putra; Najima Najima; Astri Ayu Purwati; Ermina Rusilawati (Lembaga Riset dan Inovasi Al-Matani, 2025)
The purpose of this study is to determine the effect of skill, motivation and compensation on driver performance and its impact on service quality at PT Annanta Agree Group. The population in the study was all drivers who worked on travel and all Annanta travel passengers. So that in determining the sample in this study using a meetode mix, 72 respondents were obtained, which were 36 drivers and 36 passengers. Sampling techniques using incidental sampling and data collection techniques using primary data (in the form of questionnaires) using google forms. This data analysis uses Structural Equation Modelling (SEM) using the SmartPLS application. The results showed that driver performance variables had an effect and were significant on service quality. Variable compensation does not have a significant effect on driver performance, variable compensation has an effect and is significant on service quality. Motivation variables do not have a significant effect on driver performance, motivation variables do not have a significant effect on service quality. Skill variables have an effect and are significant on driver performance, motivation variables do not have a significant effect on service quality.